HUBUNGAN ANTARA EFIKASI DIRI DENGAN PROKRASTINASI AKADEMIK PADA MAHASISWA BIMBINGAN KONSELING ISLAM UNIVERSITAS SAYYID ALI RAHMATULLAH TULUNGAGUNG - Wikan Galuh Widyarto; Maftuhah Manan (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2022)
This study has a purpose, namely knowing the level of student self-efficacy, knowing the level of student academic procrastination, and seeing the relationship between self-efficacy and academic procrastination of Islamic Counseling Guidance students at Sayyid Ali Rahmatullah University Tulungagung. The correlational quantitative method is the method used in research. The sample is 138 students using a simple random sampling technique. The scale of self-efficacy and academic procrastination becomes a means of collecting data in research, and data analysis in research uses descriptive statistics, classical assumption tests, and product moment correlation hypothesis testing. This study showed the level of student self-efficacy in the medium category at 33.3% and the level of student academic procrastination in the medium category at 40.6%, and found a relationship between self-efficacy and academic procrastination with a significance value of 0.000 (p <0.05), which means Ho is rejected and Ha is accepted. And obtained a recount of -0.759, which indicates a negative and strong correlation. So, if students have high self-efficacy, the level of academic procrastination will be low, and vice versa.